POLITICAL ISLAM AND THE GLOBAL ECONOMY - Nafis Irkhami (Epistemé: Jurnal Pengembangan Ilmu Keislaman, 2018)
This article discusses the entanglement of political Islam and the new global economy. It specifically addresses the epistemic fields of political economic concepts of the Islamist organisation of Hizbut Tahrir Indonesia/HTI. This article argues that the organisation offers an entangled epistemic field of religion, politics, and economy. The Islamic concept of khilafah is particularly defined as a new global political and economic systems that challenge the currently dominant capitalist-state of western civilisation. The crucial elements of political economy of the khilafah is the aspect of distribution rather than production, thus the HTI’s criticism lies at the notion of justice and equal access to economic resources and effects. With this framework, the HTI offers a new global political system -based on khilafah- and promises justice in economic distribution.